Thermal interface composite material based on anisotropic graphene aerogel and preparation method

By coating polyamic acid on graphene aerogel multiple times and imidizing and graphitizing, combined with epoxy resin composites, the problem of low thermal conductivity of graphene thermal interface composite materials in the prior art is solved. Its vertical thermal conductivity is significantly improved.

CN119264511APending Publication Date: 2025-01-07AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411501868.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The vertical thermal conductivity of existing graphene thermal interface composites is low and it is difficult to increase the filling content to improve thermal conductivity while maintaining low defects.

Method used

By preparing high-density and low-defect anisotropic graphene aerogel, polyamic acid is coated multiple times and imidized and graphitized, combined with epoxy resin to build high-density graphene with a vertical orientation structure. Aerogel, improves the fill content and thermal conductivity of graphene.

Benefits of technology

The vertical thermal conductivity of thermal interface composite materials is significantly improved, and thermal conductivity is achieved closer to the theoretical value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264511A_ABST
    Figure CN119264511A_ABST
Patent Text Reader

Abstract

The invention discloses a thermal interface composite material based on anisotropic graphene aerogel and a preparation method, and relates to the technical field of thermal interface materials. The preparation method comprises the following steps: performing directional freezing, freeze drying, imidization and high-temperature graphitization treatment on graphene oxide and a polyamide acid salt solution to obtain a primary anisotropic graphene aerogel skeleton; immersing the primary anisotropic graphene aerogel skeleton into a polyamic acid solution to uniformly coat the primary anisotropic graphene aerogel skeleton with polyamic acid, and carrying out solvent replacement, freeze drying and imidization treatment to obtain polyimide-coated aerogel; after the operation is repeated, graphitization treatment is performed to obtain the anisotropic graphene aerogel with high density and low defect; the anisotropic graphene aerogel and an epoxy resin system are compounded and subjected to a curing reaction, and the thermal interface composite material is prepared. The filling content of graphene in the composite material can be improved, and the purpose of greatly improving the vertical thermal conductivity of the thermal interface composite material is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal interface materials, and in particular to a thermal interface composite material based on high-density and low-defect anisotropic graphene aerogel and a preparation method thereof. Background Art

[0002] With the continuous development of microelectronics technology and the advent of the 5G communication era, the integration and power density of microprocessors or integrated circuits (chips) continue to increase, resulting in a sharp increase in the heat generated and accumulated inside them during operation, which in turn seriously affects their own performance and safety of use. Thermal interface materials are widely used in the field of heat dissipation of electronic components. Filling them between the chip and the radiator can expel the air between the two, thereby transferring heat to the outside to achieve the goal of heat dissipation and lowering the operating temperature.

[0003] Graphene has an extremely high intrinsic in-plane thermal conductivity (~5300 W m -1 K -1 ), large thickness ratio and the ability to form a thermally conductive network at a low filling content have attracted much attention. The preparation of thermally conductive composite materials by compounding graphene with polymer materials is one of the important applications of graphene in the field of thermal management materials. It is difficult to evenly disperse graphene in a polymer matrix by a simple blending method, and there is also a large interfacial thermal resistance between graphene and polymer, resulting in a low efficiency of improving thermal conductivity per unit mass of graphene content. The prepared thermal interface material has a low vertical thermal conductivity and poor thermal conductivity. In recent years, in order to improve the vertical thermal conductivity of graphene thermal interface composite materials, the main solutions are to construct a three-dimensional structure, improve the quality of graphene, reduce defects, and orient graphene sheets in the vertical direction. For example, the patent with application number 201910954092.X discloses a thermally conductive phase change composite material based on high thermal conductivity anisotropic graphene aerogel. Benefiting from the vertical orientation structure and extremely low defect level of the graphene aerogel skeleton, the thermal conductivity of the phase change material reaches 4.67W m -1 K -1 The patent application number 202010684696.X further increases the thermal conductivity of the composite material to 20.03W m by compressing the graphene aerogel skeleton. -1 K -1. From the results obtained, the vertical thermal conductivity of the graphene thermal interface composite material has been greatly improved by the above method, but it is still far from the theoretical value; on the other hand, due to the low density of the graphene three-dimensional network, it is impossible to further increase the filling content while maintaining the low defects of graphene to further improve the thermal conductivity of the thermal interface material. Although the patent with application number 201611007875.X and the patent with application number 201911222411.4 both use polyimide / graphene aerogel and preparation method similar to the present invention, the present invention adopts a new method in constructing low-defect and high-density anisotropic graphene aerogel. Summary of the invention

[0004] The object of the present invention is to provide a thermal interface composite material based on high-density and low-defect anisotropic graphene aerogel and a preparation method thereof, so as to solve the technical problems existing in the prior art.

[0005] In order to achieve the purpose of the invention, the technical solution adopted by the present invention is:

[0006] A method for preparing a thermal interface composite material based on anisotropic graphene aerogel comprises the following steps:

[0007] (1) preparing graphene oxide (GO), polyamic acid (PAA) solution and polyamic acid salt (PAAS) solution;

[0008] (2) mixing graphene oxide with a polyamic acid salt solution, and subjecting the mixture to directional freezing, freeze drying, imidization and high-temperature graphitization treatment to prepare a primary anisotropic graphene aerogel skeleton;

[0009] (3) immersing the primary anisotropic graphene aerogel skeleton in a polyamic acid solution to uniformly coat the polyamic acid, followed by solvent replacement, freeze drying, and imidization treatment to obtain a polyimide-coated aerogel; repeating the aforementioned operation, and then graphitizing the polyimide-coated aerogel to prepare a new anisotropic graphene aerogel;

[0010] (4) The new anisotropic graphene aerogel is compounded with an epoxy resin system and subjected to a curing reaction to prepare a thermal interface composite material.

[0011] Furthermore, in step (1), graphene oxide is prepared by a modified Hummers method combined with ultrasonic treatment, and the ultrasonic treatment time is 10-30 minutes.

[0012] Furthermore, the polyamic acid solution in step (1) is prepared by dissolving 4,4'-diaminodiphenyl ether in NN dimethylformamide solution, then slowly adding pyromellitic anhydride of the same molar mass, and reacting for 6-8 hours under nitrogen protection to prepare the polyamic acid solution; the mass concentration of the polyamic acid solution is 8%-12%.

[0013] Furthermore, the polyamic acid salt solution in step (1) is prepared by dissolving polyamic acid powder in an aqueous solution of triethylamine, and the mass ratio of triethylamine to polyamic acid is (0.48-0.52):1.

[0014] Furthermore, the polyamic acid powder is obtained by washing, filtering and vacuum drying the polyamic acid solution, the vacuum drying temperature is 50-60° C., and the drying time is 36-48 hours.

[0015] Furthermore, in step (2), the mass fraction of the mixed solution of graphene oxide and polyamic acid salt is 4%-6%, preferably 6%; the mass ratio of polyamic acid to graphene oxide is (7-5):(3-5), preferably 7:3.

[0016] Furthermore, in step (2), the graphene oxide and the polyamic acid salt solution are mixed by mechanical stirring combined with ultrasonic treatment, the stirring time is 2-4 hours, and the ultrasonic treatment time is 15-30 minutes.

[0017] Furthermore, in steps (2) and (3), the imidization treatment temperature is 300-350°C, the duration is 2-4 hours, preferably 4 hours, and the imidization is carried out under argon protection throughout the process; the high-temperature graphitization treatment temperature is 2800-3000°C, the duration is 2 hours, and the high-temperature graphitization treatment is carried out under argon protection throughout the process.

[0018] Furthermore, the polyamic acid solution in step (3) is obtained by diluting the polyamic acid solution prepared in step (1), and the concentration of the diluted solution ranges from 4% to 5%.

[0019] Furthermore, the method for coating the polyamic acid in step (3) is: using vacuum-assisted impregnation to immerse the anisotropic graphene aerogel skeleton in a polyamic acid solution, the vacuum degree is less than -0.01 MPa, and the pressure holding time is 12-16 hours.

[0020] Furthermore, the solvent replacement method in step (3) is: immersing the anisotropic graphene aerogel skeleton coated with polyamic acid in tert-butanol for solvent replacement, and the replacement time is 36-48 hours, preferably 48 hours.

[0021] Furthermore, in step (3), the aforementioned operation is repeated 1-4 times, preferably 4 times.

[0022] Furthermore, in step (4), the epoxy resin system includes an epoxy resin matrix, a curing agent, a reactive diluent and a reaction accelerator.

[0023] Furthermore, in step (4), the new anisotropic graphene aerogel is compounded with the epoxy resin system by vacuum-assisted impregnation, the vacuum-assisted impregnation pressure holding time is 12-16 hours, and the vacuum degree is less than -0.01 MPa.

[0024] Furthermore, in step (4), the curing reaction temperature is 80-120° C., and the curing reaction time is 4-6 hours.

[0025] A thermal interface composite material based on anisotropic graphene aerogel is prepared by the above preparation method.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention increases the density of the graphene aerogel while retaining its vertical orientation structure and high quality by coating polyamic acid multiple times on a primary anisotropic graphene aerogel skeleton and performing imidization and graphitization treatments, thereby constructing a high-density, low-defect anisotropic graphene aerogel with a vertical orientation structure, and then composites and cures the aerogel with an epoxy resin, thereby increasing the filling content of graphene in the composite material, thereby achieving the goal of significantly improving the vertical thermal conductivity of the thermal interface composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention will be further described below in conjunction with the accompanying drawings:

[0029] Figure 1 A schematic diagram of the process of preparing the thermal interface composite material of the present invention;

[0030] Figure 2 The SEM images of the anisotropic graphene aerogel prepared in Example 4 in the vertical and horizontal directions respectively;

[0031] Figure 3 This is a SEM image of the cross section of the thermal interface composite material prepared in Example 4. DETAILED DESCRIPTION

[0032] In order to make the various technical features and advantages or technical effects of the above technical solutions of the present invention more obvious and easy to understand, the following is a detailed description in conjunction with the embodiments and drawings. The experimental methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.

[0033] Embodiment 1:

[0034] The GO suspension was prepared by ultrasound for 30 minutes, and the prepared polyamic acid solution concentration was 10%. PAAS was prepared by triethylamine and polyamic acid at a ratio of 0.52:1. The PAAS solution and the GO suspension were mixed in proportion, and after ultrasonic treatment for 15 minutes, stirred for 4 hours to obtain a mixed suspension, ensuring that the mass ratio of PAA to GO in the mixed suspension was 5:5, and the mass fraction of the two in the mixed solution was 5%. The above mixed suspension was poured into a mold for directional freezing, and after complete freezing, freeze-dried to obtain PAAS / GO hybrid aerogel. It was treated at 350°C in an argon atmosphere for 4 hours, and then treated at 2800°C for 2 hours under argon protection to obtain a vertically oriented graphene aerogel skeleton. After the polyamic acid solution was diluted to 4% with NN dimethylacetamide, the obtained aerogel skeleton was immersed in the polyamic acid solution and kept under vacuum for 14 hours, then taken out and immersed in tert-butyl alcohol for 36 hours for solvent replacement, and then placed in a freeze dryer for 72 hours for drying, and then reacted in an argon atmosphere at 350°C for 4 hours for imidization to obtain a single polyimide-coated graphene aerogel, and then treated at 2800°C for 2 hours under argon protection to obtain a graphene aerogel. It was immersed in an epoxy resin mixed system, maintained under vacuum for 12 hours, and then cured at 80°C for 4 hours, and cured at 120°C for 2 hours to prepare a thermal interface composite material, and its thermal conductivity was tested.

[0035] Embodiment 2:

[0036] The GO suspension was prepared by ultrasound for 30 minutes, and the prepared polyamic acid solution concentration was 8%. PAAS was prepared by triethylamine and polyamic acid at a ratio of 0.50:1. The PAAS solution and the GO suspension were mixed in proportion, and after ultrasonic treatment for 15 minutes, stirred for 3 hours to obtain a mixed suspension, ensuring that the mass ratio of PAA to GO in the mixed suspension was 6:4, and the mass fraction of the two in the mixed solution was 4%. The above mixed suspension was poured into a mold for directional freezing, and after complete freezing, freeze-dried to obtain PAAS / GO hybrid aerogel. It was treated at 320°C in an argon atmosphere for 2 hours, and then treated at 2850°C for 2 hours under argon protection to obtain a vertically oriented graphene aerogel skeleton. After the polyamic acid solution was diluted to 5% with NN dimethylacetamide, the obtained aerogel skeleton was immersed in the polyamic acid solution and kept under vacuum for 12 hours, then taken out and immersed in tert-butanol for 40 hours for solvent replacement, and then placed in a freeze dryer for 72 hours for drying, and then reacted in an argon atmosphere at 320°C for 2 hours for imidization to obtain a single polyimide-coated graphene aerogel. Repeat the above operation twice, and then treat at 2850°C for 2 hours under argon protection to obtain a graphene aerogel. Immerse it in an epoxy resin mixed system, keep it under vacuum for 14 hours, and then perform a curing reaction at 80°C for 4 hours, and then perform a curing reaction at 120°C for 2 hours to prepare a thermal interface composite material, and test its thermal conductivity.

[0037] Embodiment 3:

[0038] The GO suspension was prepared by ultrasound for 15 minutes, and the prepared polyamic acid solution concentration was 10%. PAAS was prepared by triethylamine and polyamic acid at a ratio of 0.48:1. The PAAS solution and the GO suspension were mixed in proportion, and after ultrasonic treatment for 20 minutes, stirred for 2 hours to obtain a mixed suspension, ensuring that the mass ratio of PAA to GO in the mixed suspension was 7:3, and the mass fraction of the two in the mixed solution was 5%. The above mixed suspension was poured into a mold for directional freezing, and after complete freezing, freeze-dried to obtain PAAS / GO hybrid aerogel. It was treated at 350°C in an argon atmosphere for 2 hours, and then treated at 2850°C for 2 hours under argon protection to obtain a vertically oriented graphene aerogel skeleton. After the polyamic acid solution was diluted to 4% with NN dimethylacetamide, the obtained aerogel skeleton was immersed in the polyamic acid solution and kept under vacuum for 12 hours, then taken out and immersed in tert-butanol for 36 hours for solvent replacement, and then placed in a freeze dryer for 72 hours for drying, and then reacted in an argon atmosphere at 350°C for 2 hours for imidization to obtain a single polyimide-coated graphene aerogel. Repeat the above operation 3 times, and then treat at 2850°C for 2 hours under argon protection to obtain graphene aerogel. Immerse it in an epoxy resin mixed system, keep it under vacuum for 14 hours, and then perform a curing reaction at 80°C for 2 hours, and then perform a curing reaction at 120°C for 2 hours to prepare a thermal interface composite material, and test its thermal conductivity.

[0039] Figure 3 This is a SEM image of the cross section of the thermal interface composite material prepared in Example 4, indicating that the epoxy resin has been completely filled in the pores of the aerogel.

[0040] Embodiment 4:

[0041] The GO suspension was prepared by ultrasound for 15 minutes, and the prepared polyamic acid solution concentration was 12%. PAAS was prepared by triethylamine and polyamic acid at a ratio of 0.48:1. The PAAS solution and the GO suspension were mixed in proportion, and after ultrasonic treatment for 30 minutes, stirred for 2 hours to obtain a mixed suspension, ensuring that the mass ratio of PAA to GO in the mixed suspension was 7:3, and the mass fraction of the two in the mixed solution was 6%. The above mixed suspension was poured into a mold for directional freezing, and after complete freezing, freeze-dried to obtain PAAS / GO hybrid aerogel. It was treated at 300°C in an argon atmosphere for 4 hours, and then treated at 3000°C for 2 hours under argon protection to obtain a vertically oriented graphene aerogel skeleton. After the polyamic acid solution was diluted to 4.5% with NN dimethylacetamide, the obtained aerogel skeleton was immersed in the polyamic acid solution and kept under vacuum for 12 hours, then taken out and immersed in tert-butyl alcohol for 48 hours for solvent replacement, and then placed in a freeze dryer for 72 hours for drying, and then reacted in an argon atmosphere at 300°C for 4 hours for imidization to obtain a single polyimide-coated graphene aerogel. Repeat the above operation 4 times, and then treat at 3000°C for 2 hours under argon protection to obtain graphene aerogel. Immerse it in an epoxy resin mixed system, keep it under vacuum for 12 hours, and then perform a curing reaction at 80°C for 4 hours, and then perform a curing reaction at 120°C for 2 hours to prepare a thermal interface composite material, and test its thermal conductivity.

[0042] Figure 2 The SEM images of the anisotropic graphene aerogel prepared in Example 4 in the vertical and horizontal directions respectively show that after multiple coatings with polyimide and high-temperature graphitization treatments, the anisotropic graphene aerogel still has anisotropic characteristics.

[0043] Comparative Example 1:

[0044] The PAAS solution and GO suspension were mixed in proportion, ultrasonically treated for 20 minutes and then stirred for 2 hours to obtain a mixed suspension, ensuring that the mass ratio of PAA to GO in the mixed suspension was 7:3, and the mass fraction of the two in the mixed solution was 4%. The above mixed suspension was poured into a mold for directional freezing, and after complete freezing, freeze-dried to obtain PAAS / GO hybrid aerogel. It was treated at 300°C for 4 hours in an argon atmosphere, and then treated at 2800°C for 2 hours under argon protection to obtain a vertically oriented graphene aerogel skeleton. It was immersed in an epoxy resin mixed system, maintained under vacuum for 12 hours, and then cured at 80°C for 4 hours, and cured at 120°C for 2 hours to prepare a thermal interface composite material, and its thermal conductivity was tested.

[0045] Comparative Example 2:

[0046] The PAAS solution and GO suspension were mixed in proportion, ultrasonically treated for 20 minutes and then stirred for 2 hours to obtain a mixed suspension, ensuring that the mass ratio of PAA to GO in the mixed suspension was 7:3, and the mass fraction of the two in the mixed solution was 6%. The above mixed suspension was poured into a mold for directional freezing, and after complete freezing, freeze-dried to obtain PAAS / GO hybrid aerogel. It was treated at 300°C for 4 hours in an argon atmosphere, and then treated at 2800°C for 2 hours under argon protection to obtain a vertically oriented graphene aerogel skeleton. It was immersed in an epoxy resin mixed system, maintained under vacuum for 12 hours, and then cured at 80°C for 4 hours, and cured at 120°C for 2 hours to prepare a thermal interface composite material, and its thermal conductivity was tested.

[0047] Comparative Example 3:

[0048] The PAAS solution and GO suspension were mixed in proportion, ultrasonically treated for 20 minutes and then stirred for 2 hours to obtain a mixed suspension, ensuring that the mass ratio of PAA to GO in the mixed suspension was 5:5, and the mass fraction of the two in the mixed solution was 6%. The above mixed suspension was poured into a mold for directional freezing, and after complete freezing, freeze-dried to obtain PAAS / GO hybrid aerogel. It was treated at 300°C for 4 hours in an argon atmosphere, and then treated at 2800°C for 2 hours under argon protection to obtain a vertically oriented graphene aerogel skeleton. It was immersed in an epoxy resin mixed system, maintained under vacuum for 12 hours, and then cured at 80°C for 4 hours, and cured at 120°C for 2 hours to prepare a thermal interface composite material, and its thermal conductivity was tested.

[0049] Table 1: Comparison of thermal conductivity of thermal interface composite materials obtained in comparative examples and examples in vertical direction

[0050]

[0051] The vertically oriented graphene aerogel constructed by the preparation method of the present invention has the characteristics of high density and low defects, and the thermal interface composite material prepared by the aerogel has extremely high thermal conductivity in the vertical direction.

[0052] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A method for preparing a thermal interface composite material based on anisotropic graphene aerogel, characterized in that: The steps include: (1) preparing graphene oxide, a polyamic acid solution and a polyamic acid salt solution; (2) mixing graphene oxide with a polyamic acid salt solution, and subjecting the mixture to directional freezing, freeze drying, imidization and high-temperature graphitization treatment to prepare a primary anisotropic graphene aerogel skeleton; (3) immersing the primary anisotropic graphene aerogel skeleton in a polyamic acid solution to uniformly coat the polyamic acid, followed by solvent replacement, freeze drying, and imidization treatment to obtain a polyimide-coated aerogel; repeating the aforementioned operation, and then graphitizing the polyimide-coated aerogel to prepare a new anisotropic graphene aerogel; (4) The new anisotropic graphene aerogel is compounded with an epoxy resin system and subjected to a curing reaction to prepare a thermal interface composite material.

2. The preparation method according to claim 1, characterized in that In step (1), graphene oxide is prepared by a modified Hummers method combined with ultrasonic treatment, and the ultrasonic treatment time is 10-30 minutes; the polyamic acid solution is prepared by: dissolving 4,4'-diaminodiphenyl ether oxide in a NN dimethylformamide solution, then slowly adding pyromellitic anhydride of the same molar mass, and reacting for 6-8 hours under nitrogen protection to prepare a polyamic acid solution with a mass concentration of 8%-12%; the polyamic acid salt solution is prepared by dissolving polyamic acid powder in an aqueous solution of triethylamine, and the mass ratio of triethylamine to polyamic acid is (0.48-0.52):1; wherein the polyamic acid powder is obtained by washing the polyamic acid solution with water, filtering, and vacuum drying, and the vacuum drying temperature is 50-60°C and the drying time is 36-48 hours.

3. The preparation method according to claim 1, characterized in that: The mass fraction of the mixed solution of graphene oxide and polyamic acid salt in step (2) is 4%-6%; the mass ratio of polyamic acid to graphene oxide is (7-5):(3-5); the mixing method of graphene oxide and polyamic acid salt solution is mechanical stirring combined with ultrasonic treatment, the stirring time is 2-4 hours, and the ultrasonic treatment time is 15-30 minutes.

4. The preparation method according to claim 1, characterized in that: In steps (2) and (3), the imidization treatment temperature is 300-350°C, the duration is 2-4 hours, and the imidization process is carried out under argon protection; the high-temperature graphitization treatment temperature is 2800-3000°C, the duration is 2 hours, and the high-temperature graphitization treatment is carried out under argon protection.

5. The preparation method according to claim 1, characterized in that: The polyamic acid solution in step (3) is obtained by diluting the polyamic acid solution prepared in step (1), and the mass concentration of the solution after dilution is 4%-5%.

6. The preparation method according to claim 1, characterized in that: The method for coating polyamic acid in step (3) is: using vacuum-assisted impregnation, immersing the anisotropic graphene aerogel skeleton in a polyamic acid solution, the vacuum degree is less than -0.01MPa, and the pressure holding time is 12-16 hours; the solvent replacement method is: immersing the anisotropic graphene aerogel skeleton coated with polyamic acid in tert-butanol for solvent replacement, and the replacement time is 36-48 hours.

7. The preparation method according to claim 1, characterized in that: In step (3), the above operation is repeated 1-4 times.

8. The preparation method according to claim 1, characterized in that: The epoxy resin system in step (4) includes an epoxy resin matrix, a curing agent, a reactive diluent and a reaction accelerator.

9. The preparation method according to claim 1, characterized in that: In step (4), the new anisotropic graphene aerogel is compounded with the epoxy resin system by vacuum-assisted impregnation, the vacuum-assisted impregnation pressure holding time is 12-16 hours, the vacuum degree is less than -0.01 MPa; the curing reaction temperature is 80-120° C., and the curing reaction time is 4-6 hours.

10. A thermal interface composite material based on anisotropic graphene aerogel, prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A method for preparing polyimide-graphene composite aerogels through in-situ polymerization

    CN106750290B

  • A phase change composite material based on a highly thermally conductive anisotropic graphene framework and its preparation method

    CN110804420B

  • An ordered porous polyimide / graphene composite aerogel, its preparation method and applications

    CN110818945B

  • Graphene / epoxy resin composite material based on lamellar anisotropy and preparation method thereof

    CN111777841A